Social responsibility and ESG in SMEs for entrepreneurship growth: A systematic mapping study - Javlon Nurlanovich Bayisbayev (BIO Web of Conferences)
In the wake of growing concerns over corporate sustainability and regulatory compliance, it is increasingly debated whether small and medium enterprises (SMEs) can achieve long-term competitiveness and financial resilience through the adoption of Social Responsibility (SR) and Environmental, Social, and Governance (ESG) frameworks in the same manner as larger multinational corporations did. Based on these facts, this paper aims to analyze the extent of ESG integration in SMEs, evaluate its direct and indirect effects on entrepreneurial growth, and assess the role of leadership and governance structures in shaping sustainability-driven business models. The authors construct a systematic mapping framework using the Term Frequency-Inverse Document Frequency (TF-IDF) and content analysis estimation for describing the relationship between the Sustainability Engagement Index and various ESG-related performance factors. In our study, we identified key determinants of ESG adoption related to stakeholder engagement (0.82), regulatory compliance (0.79), leadership commitment (0.76), and financial performance (0.72). Evidence suggests that comprehensive ESG integration is likely to affect SME resilience and investor confidence, but it is questionable whether the fragmented adoption of subsequent sustainability-driven policy movements (e.g., towards carbon neutrality, supply chain transparency, and ethical labor practices) will equally benefit from short-term profitability improvements. The paper finishes with strategic recommendations for SMEs and policy implications for ESG adoption. Future studies can empirically test the proposed linkages to reveal industry-, geographical-, and regulatory-specific variations between processes of SR and ESG implementation and entrepreneurial performance outcomes.